Decreasing Postoperative Narcotic Utilization with the Use of Concentrated Bone Marrow Aspirate in First Metatarsophalangeal Joint Interposition Arthroplasty. Issue 3 (14th September 2018) - Maccario, Camilla; Aynardi, Michael; Tan, Eric; Schon, Lew
Category: Midfoot/Forefoot Introduction/Purpose: Interposition arthroplasty is an interim procedure for the treatment of first metatarsophalangeal osteoarthritis demonstrating excellent survivorship. The procedure is commonly performed at our institution and successful long-term results have been described. Furthermore, we have utilized concentrated, autologous, bone marrow aspirate (BMAC) to augment and accelerate patient recovery, decrease postoperative pain, reduce postoperative narcotic requirement, and improve tissue healing for a variety of ankle and foot pathology. The purpose of this study was to compare the early outcomes of interpositional arthroplasty with patients receiving BMAC augmentation versus controls and to evaluate postoperative analgesia and narcotic requirements. Methods: After IRB approval, patients undergoing interposition arthroplasty for hallux rigidus at our institution from 2009-2014 were identified. All cases were performed using autograft capsular interposition by a single surgeon. 18 BMAC cases with complete records were identified. These were matched to controls in a 1:1 manner by age, gender, and laterality. A retrospective analysis of prospectively collected data was performed. Demographics, clinical range of motion, complications, VAS scoring, FAAM, FFI, AOFAS scores were recorded and analyzed. Postoperative analgesia requirements, narcotic usage, and prescription data were collected. Follow-up was conducted at 2, 6, 12, 24, & 52 weeks postoperatively. Time experiencing pain and time to achieve maximum functional satisfaction were recorded. Results: 89% (32/36) of patients undergoing interposition arthroplasty were female, average age 58 years (range, 39-74). The average number of weeks experiencing pain, narcotic utilization, and time to achieve functional satisfaction was statistically lower in the BMAC group, 11 weeks (range, 6-24) versus controls, 27.4 weeks (range, 6-52), (p=0.001). The number of post-operative days of pain requiring narcotic analgesia was significantly lower in patients receiving BMAC 4.2 days (range, 1-14) compared to controls averaging 13.8 days (range, 2-48) (p=0.02). Both groups demonstrated improvements in pre- and postoperative VAS scores, increase in motion, SF-36, FAAM, FFI, and AOFAS scores at 52 week follow up. There were no failures and there was one superficial infection requiring oral antibiotics. Conclusion: This study confirms that patients undergoing interpositional arthroplasty demonstrate excellent clinical improvements in short-term follow-up with few complications. Moreover, augmentation of this procedure with BMAC results in a significant decrease in narcotic utilization and recovery time post-operatively. BMAC may be a useful adjunct in diminishing postoperative narcotics we prescribe to our patients.